Requirements analysis for SBS system and study review process iteration during requirements phase - Alghamdi, Hanan Musafer H. (2009)
This paper represented the experience gained and discussed the works done under the title “Requirements Analysis For SBS System And Study Review Process Iteration During Requirements Phase” by the author during her Industrial Attachment 2 Period, from 13th October 2008 to 13th March 2009, at HeiTech Padu, Malaysia. The purpose of this paper is to analyze requirements for Shared Banking Services system and study reviews process that can be applied in requirement phase in order to get quality requirements document with reduced errors. The SBS system is aimed to provide the banking services, of one selected bank, through post office in order to give the customer other alternative way to perform his or her banking services. There were some studies is carried out to understand how the reviews process is important in requirement phase and to show how to make the reviews process more effective by iterate it during the development of SRS document. The required methodology to achieved objectives of this paper began from initiation and planning, an analysis of Shared Banking Services system, study about best practices in requirements engineering process and study requirements review process. Finally, documentation of the output was performed. The development team of SBS system used ADVISE methodology which is based in HeiTech Padu process development. The deliverables of analyzing SBS system are Software Requirement Specification (SRS), Requirement Traceability Matrix and User Manual documents. A workflow is introduced to show how the reviews process can be iterated during development of SRS document.